Expanze českého výrobce modulových dřevostaveb na intrakomunitární trh - Kočařík, David (Vysoké učení technické v Brně. Fakulta podnikatelská, 2018)
Diplomová práce se zabývá návrhem rozvoje společnosti DOMESTA PLUS s.r.o., která se zabývá výrobou modulových dřevostaveb. Teoretická část práce obsahuje vymezení pojmů souvisejících s intrakomunitárním trhem, podmínkami pro vstup na tento trh a popisem vybraných analýz vnějšího a vnitřního prostředí firmy. Tyto analýzy jsou použity v praktické části práce jako podklad pro návrh vhodné strategie rozvoje, spočívajícího v expanzi společnosti na intrakomunitární trh. Na základě výsledků analýz je zpracován konkrétní návrh změny vedoucí ke zvýšení konkurenceschopnosti a zlepšení ekonomické situace firmy. Návrhová část se zabývá také identifikací rizik souvisejících se zavedením změny.

The diploma thesis deals with a proposal of business development of the company DOMESTAV PLUS s.r.o., which deals with the production of modular wooden buildings. The theoretical part contains defining the terms connected with the intra-community market, the conditions for entering this market and description of selected analyses of company’s external and internal environment. These analyses are applied in the practical part as basis for the proposal of an appropriate strategy for the development, consisting in the expansion of the company into the intra-community market. On the basis of the results of the analyzes is made the proposal of changes, which leads to increased competitiveness and improvement of the company's economic situation. The proposal part also deals with identification of the risks associated with the implementation of this change.
Expansion of a Czech Producer of Modular Wood Buildings on the Intra-community Market
Keywords: zahraniční trh; Evropská unie; průzkum trhu; zahraniční obchod; ETA; strategie; SLEPT analýza; 7S analýza; Porterův model; SWOT analýza; riziková politika; harmonogram; foreign market; European Union; market research; foreign trade; ETA; strategy; SLEPT analysis; 7S analysis; Porter model; SWOT analysis; risk policy; schedule